Tarkhan Prison and Surrounding Tatars in Late 17th — Early 18th Centuries: Based on Excerpts from Scribe Books and Cartography by S. U. Remezov - V. A. Zakh; T. N. Rafikova (Научный диалог, 2022)
The experience of reconstructing the system of settlement and land use of the Tatar and Russian population in one of the regions of the Lower Tobol region is presented on the basis of an analysis of maps and archival sources of the 17th century. As a result of comparing the map of S. U. Remezov with modern cartographic material, the displacement of the channels of the Tobol, Tura and Tapa and a large water supply of the surrounding water bodies compared to the modern one were recorded. At the same time, it is concluded that large-scale landscape changes over the past four centuries have not occurred in the right-bank part of Tobol and the interfluve of Tobol and Tura. For the first time, an extract from the cadastral book of L. M. Poskochin of 1684—1685 is published, recorded as part of the “Documents on land disputes of the yasash Tatars of the Yalutorovsky district of the Tobolsk province”, stored in the archive of the Museum Complex named after. I. Ya. Slovtsov in Tyumen. On the basis of archival data and the map of S. U. Remezov, the number and location of the yurts of the yasash Tatars of the Tarkhansky prison were restored, the number of their population was calculated, in particular, the growth of the male Tatar population was established. In addition, an assessment of the natural potential of the region under consideration, the role of the producing and appropriating industries in the economy of the local and service population is given.